2006
DOI: 10.1111/j.1365-313x.2006.02825.x
|View full text |Cite
|
Sign up to set email alerts
|

A simple in vitro RNA editing assay for chloroplast transcripts using fluorescent dideoxynucleotides: distinct types of sequence elements required for editing of ndh transcripts

Abstract: SummaryRNA editing is found in various transcripts from land plant chloroplasts. In tobacco chloroplasts, C-to-U conversion occurs at 36 specific sites including two sites identified in this work. Our RNA editing assay system using chloroplast extracts facilitated biochemical analyses of editing reactions but required mRNAs labeled with 32 P at specific sites. Here, we have improved the in vitro system using fluorescence-labeled chain terminators, ddGTP and ddATP, and have measured the editing activity at 19 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…For both sites, mutations introduced into the 215 to 26 region abolished competition for the binding of the editing factor, whereas mutations in the 25 to 21 region had a weaker effect. Consistent with this, mutagenesis of the ndhF RNA substrate showed that purine/pyrimidine exchanges in the 215 to 21 upstream region abolish in vitro editing of the ndhF-1 site (Sasaki et al, 2006).…”
Section: Discussionmentioning
confidence: 53%
“…For both sites, mutations introduced into the 215 to 26 region abolished competition for the binding of the editing factor, whereas mutations in the 25 to 21 region had a weaker effect. Consistent with this, mutagenesis of the ndhF RNA substrate showed that purine/pyrimidine exchanges in the 215 to 21 upstream region abolish in vitro editing of the ndhF-1 site (Sasaki et al, 2006).…”
Section: Discussionmentioning
confidence: 53%
“…Target Sequences at the RNA-editing Sites-For several editing sites in mitochondria and plastids, in vitro and in organello investigations have identified the cis-elements in the RNA context to occupy the region between 20 or 25 nucleotides upstream (5Ј) and 1 or 3 nucleotides downstream (3Ј) of the edited C (5,6,8,10,11,(43)(44)(45)(46). Therefore, for the sites affected in the mef18 to mef22 mutants, a similar extent of the recognition sequences may be expected.…”
Section: Refs T-dna Insertion Lines T-dna Locationmentioning
confidence: 99%
“…These mutant IDS cDNAs were selected on the basis of the type of mutation and its location: (i) a stop codon mutation (p.W12X), located in the signal peptide, 4 codons downstream of the p.R8X (c.22C>T) mutation, and resulting from a G>A transition at position c.35; (ii) a premature stop codon (p.L279X) located in exon 6 resulting from a micro-deletion (c.836delT) and (iii) a missense mutation (p.C432R) located in exon 9 and caused by the transition c.1294T>C. No trace of wild-type IDS sequence was evident in cDNA derived from these three patients. To address further the possibility of experimental artefacts in the analysis of material derived from pts #1, #2 and #3, the results obtained by classical sequencing [Sanger et al, 1977] were corroborated both by pyrosequencing [Ronaghi et al, 1998;Sodhi et al, 2005] and single-nucleotide primer extension assay (SNuPE) [Sasaki et al, 2006]. Pyrosequencing, which employs a luciferasebased enzyme reaction to monitor DNA/cDNA synthesis in real time, served to confirm that transcripts bearing the wild-type IDS sequence were indeed present among cloned RT-PCR products in all three patients in addition to the expected IDS transcripts bearing the mutant sequences (Figure 2).…”
Section: Mutational Analysis Of the Ids Gene And Characterization Of mentioning
confidence: 99%
“…Single nucleotide primer extension analysis (SNuPE) is a method for allelic transcript discrimination that requires only a 1-bp difference between alleles [Sasaki et al, 2006]. RT-PCR products, obtained using the forward primer 1U (5'-GCTGCGGCGGCGGCTGCTAACTGCG-3'), located in the transcribed region upstream of exon 1, and the reverse primer, 3AL (5'-GGTCACATAGCCATTCTCCTTG-3'), located within exon 3, were purified using a Montage PCR centrifugal filter device (Millipore Corporation, Bedford, MA, USA).…”
Section: C) Single Nucleotide Primer Extension Analysismentioning
confidence: 99%